Concurrent removal of nitrate, fluoride and arsenic by mixed hydrous bismuth oxide from water - Ranjan M.; Kumar P. (My University, 2025)
Clean and safe drinking water for all is an essential requirement for the world in which we want to live, but a majority of the population has been dependent on groundwater for its daily needs. Toxic contamination of such water could result in large-scale health effects. A great proportion of groundwater suffers from the problems of nitrate, fluoride, and arsenic contamination. Thus, the present research was aimed to remove these contaminants from the water. Hydrous bismuth oxide based adsorbents exhibited high adsorption capacities towards nitrate, fluoride and arsenic. However, As (V) removal was found to be more effective as compared to nitrate and fluoride. The removal efficiencies are 52, 72 and 92% for nitrate, fluoride and As (V), respectively, during concurrent removal of the same. Ion exchange with chloride ions was the probable mechanism for the concurrent removal of the above three anions from water. Scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS) and Fourier transform infrared spectroscopy (FTIR) were used for the characterization of HBO12mix adsorbents. The results of the present study indicated that HBO12mix has the potential for concurrent removal of nitrate, fluoride, and As (V) from groundwater. Hence, hydrous bismuth oxide can be used in the drinking water treatment process at a domestic level. © 2020 IWA Publishing. All rights reserved.